Fatores associados à conclusão da educação superior por cegos: um estudo a partir de L. S. Vygotski - Silva Junior, Bento Selau da (2013)
This thesis has the objective to describe how a group of blind people explains its graduation in higher education, identifying the factors associated with this conclusion, in the light of L. S. Vygotski s studies. Methodologically, the thesis consisted in a qualitative study, assuming the form of case studies. The research counted on the participation of nine blind people based on the following criteria: being blind and being higher education egresses. The instruments to collect data were the interview and the document analysis. The collected data were worked out through the discursive textual analysis. The theoretical framework brought information pertaining to the participation of blind students in higher education; definition of terms blind and disability; social movements influence on the blind; inclusion of disabled people in higher education; the presence of obstacles for the blind to attend higher education; and the role of professors who work with visually impaired students.It included the presentation of psychological-pedagogical propositions about blindness, arising from investigations developed by Vygotski in the context of his defectology, which resulted in a reorganization of the texts of Tome V of his Collected Works, so that, it would be possible to understand his proposals around the theme.Other concepts of Cultural-Historical theory which were considered as fundamental to this work were also discussed:consciousness, will and subjectivity, besides the terms overcome and overcoming that appear in the author set of defectology. The findings of the research were organized into four emerging categories: Quality of basic education attended , Difficulties found , External facilitator factors and Internal facilitator factors . Such findings indicated that the quality of learning and educational inclusion in basic education influenced the path of the blind through higher education. The difficulties found during attendance at higher education above all, in the selection process for university entrance the need to work/being employed during the study period, difficulties relating to the relationship to some teachers, the lack of technological instrumental and adaptation of materials in resource rooms, interferedin the subjects route through higher education.The assistance received outside the university and the support of some teachers, were facilitator factors. The basic education living of the blind, the difficulties and the facilitator factors, were not, however, decisive for the completion of higher education; the main factors identified in the data and interpreted with the support of the studies developed by Vygotski, were the internal (subjective): consciousness and will. It was defended the thesis that the consciousness about the discrepancies between the lived and the expected reality, generated the wish to complete higher education, that is to say, factors connected to the subjectivity of the students, leading the group of blind which was studied, to achieve this goal.